Evaluation of the effects of the low-level laser therapy on swelling, pain, and trismus after removal of impacted lower third molar - Alan, Hilal (Head Face Med, 2016)
BACKGROUND: In current study we aimed to examine the effect of a low-level laser therapy on the pain, mouth opening and swelling of patients whose impacted 3rd molar tooth was extracted in addition measurement volumetrically to the edema with 3dMD face system. METHODS: It was surveyed 15 patients who had bilateral symmetric lower 3rd molars. Surgical sides of patients were randomly separated into two groups: the study group and the control group. It was applied extra oral low-level laser therapy (LLLT, 0.3 W, 40 s, 4 J/cm(2)) to the study group (n = 15) after the surgical operation and on the 2nd day. Only routine postoperative recommendation (ice application) was made in the control (n = 15) group. The maximum mouth opening, pain level and facial swelling evaluated. 3dMD Face® (3dMD, Atlanta, GA) Photogrammetric System was used to evaluate volumetric changes of the swelling. RESULTS: There was no statistically significant difference in the edema and interincisal opening between the groups and the pain level in the laser group was significantly lower than in the control group on the 7(th) postoperative day. CONCLUSIONS: Although there were decreasing trismus, swelling, and pain level, with this LLLT, there was significant difference only in the 7th day pain level in the laser group compared with the control group.